2015
DOI: 10.21103/article5(4)_oa1
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Preservation of Antibodies to the Flu Virus in the Mother-Child Pairs during the Vaccination of Women Depending on the Trimester of Pregnancy

Abstract: Vaccination against flu in the second and third trimesters of pregnancy with the use of Agrippal S1 is effective and meets the CPMP criteria. In our study, one month after vaccination, there was progress in the production of post-vaccination antibodies in protective values in pregnant women vaccinated in the third trimester of gestation. In neonates whose mothers had been vaccinated in the last trimester of pregnancy, there were also higher levels of protective antibodies to the flu A virus strains. Three mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Such trend was also traced in a group of non-pregnant women; however, the changes were less remarkable, with a fairly signiicant fraction of subjects having a high level of protective antibodies. Similar dynamics of post-vaccination antibodies were noted in pregnant women vaccinated with subunit non-adjuvanted inluenza vaccine [37].…”
Section: Vaccines 82supporting
confidence: 64%
See 1 more Smart Citation
“…Such trend was also traced in a group of non-pregnant women; however, the changes were less remarkable, with a fairly signiicant fraction of subjects having a high level of protective antibodies. Similar dynamics of post-vaccination antibodies were noted in pregnant women vaccinated with subunit non-adjuvanted inluenza vaccine [37].…”
Section: Vaccines 82supporting
confidence: 64%
“…Such trend was also traced in a group of non-pregnant women; however, the changes were less remarkable, with a fairly signiicant fraction of subjects having a high level of protective antibodies. Similar dynamics of post-vaccination antibodies were noted in pregnant women vaccinated with subunit non-adjuvanted inluenza vaccine [37].The rate of development and intensity of protective immunity include the level and factor of seroconversion across all inluenza virus strains. Those were compared between the groups, and it was found that their values met the CPMP criteria ( Table 7).…”
mentioning
confidence: 55%
“…With the exception of women vaccinated in the 2nd trimester in Kostinov et al, seroprotection and seroconversion rates were consistently in excess of 75% irrespective of the timing of vaccination. Compared with women vaccinated in the 2nd trimester, Kostinov et al reported that women vaccinated in the 3rd trimester had a significantly higher seroconversion rate ( P < 0.01) against the H3N2 subtype (3rd trimester: 73%; 2nd trimester: 30%) and influenza B (3rd trimester: 82%; 2nd trimester: 52%). Ohfuji et al only found a significant difference in seroconversion rates by trimester four weeks after administering a second vaccine dose (1st trimester: 76%, 2nd trimester: 91%, 3rd trimester: 94% ( P = 0.02)).…”
Section: Resultsmentioning
confidence: 93%
“…Twelve studies measured both baseline HI titres immediately prior to vaccination and post‐vaccination HI titres (Table ). Post‐vaccination blood draw occurred at 1 month after vaccination in four studies, at 4 weeks in three studies and at 3 weeks in five studies . Horiya et al and Jackson et al also measured HI titres 3 weeks after a second dose, whereas Ohfuji et al measured titres at 4 weeks after the second dose (compared to 3 weeks after the first dose).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation